Perlawanan Rakyat Indonesia terhadap Kekuasaan Jepang - Galih Raka Siwi; Nita Pardede; Josua Simanjuntak; Rosmaida Sinaga (Journal on Education, 2024)
The Indonesian people's resistance to Japanese rule was motivated by the oppression carried out by Japan. The Indonesian people realized that the Japanese had acted arbitrarily and inhumanely, even the Japanese also often massacred the Indonesian people and employed them inhumanely which we commonly know as romusha. Other factors also triggered the Indonesian people to fight against Japan. This research uses a qualitative method. By means of literature studies or literature studies by looking for various sources such as journals, books, articles, theses and so on. The findings from these sources we raise into four discussions, namely the reign of the Japanese occupation, the nature of the Japanese occupation, the resistance of the Indonesian people against Japan, the end of the Japanese occupation in Indonesia. It is hoped that after reading this journal, it can increase readers' interest in adding knowledge about history and also build a sense of nationalism and love for the country for readers.